(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: The metabolic syndrome is a constellation of metabolic abnormalities that predicts future development of type 2 diabetes mellitus and cardiovascular disease. Menopausal transition and postmenopausal state are considered as a vulnerable period for developing metabolic syndrome. Aim: This study aimed to estimate the prevalence of metabolic syndrome and identify its predominant components among pre-and postmenopausal women, and to investigate whether the variation of FSH is associated with metabolic factors in postmenopausal women attending Tishreen University Hospital. Materials and Methods: This is a cross-sectional study conducted at Endocrinology Department , Tishreen university Hospital in Lattakia ,Syria . The study enrolled 106 premenopausal and 124 postmenopausal women. Details of menopausal history, reproductive, and medical profile were obtained. Then, waist circumference (WC), body mass index (BMI), and blood pressure were recorded. A venous blood sample was collected for FSH, fasting blood glucose, triglycerides (TGs), low density lipoprotein cholesterol (LDL), and high density lipoprotein cholesterol (HDL). Metabolic syndrome was defined according to the American Heart Association/ National Heart, Lung, and Blood Institute criteria. Results: Metabolic syndrome was observed in 30.9% of the total study population, 22.6% of the premenopausal women and 37.9% of the postmenopausal women displayed metabolic syndrome. In addition, the frequency of metabolic syndrome increased with age. Regarding the components of metabolic syndrome, postmenopausal women were more likely to have WC ≥ 88 cm , HDL levels < 50 mg/Dl , systolic blood pressure (SBP) values ≥ 130 mmHg , and diastolic blood pressure (DBP) values ≥ 85 mmHg , and fasting glucose levels ≥ 100 mg/Dl. Compared with women with high FSH levels, women with low FSH levels had higher WC, TG, and blood pressure, but lower HDL (all p value <0.05). Compared with women in the groups of normal levels of metabolic syndrome biomarkers, women in the abnormal groups had lower FSH (all p value <0.05). Conclusion: Metabolic syndrome is more prevalent among postmenopausal women than among premenopausal women. Low FSH appears to be a risk factor of most components of Metabolic syndrome in postmenopausal women, which merits further study.